From stagnation to growth: Unified growth theory - Oded Galor (Brown University, Department of Economics, 2004)
This chapter examines the process of development from an epoch of Malthusian stagnation to a state of sustained economic growth. The analysis focuses on recently advanced unified growth theories that capture the intricate evolution of income per capita, technology, and population over the course of human history. Deciphering the underlying forces that triggered the transition from stagnation to growth and the associated phenomenon of the great divergence in income per capita across countries has been widely viewed as one of the most significant challenges facing researchers in the field of growth and development. The inconsistency of non-unified growth models with the main characteristics of the process of development across most of human history induced growth theorists to advance an alternative theory that captures in a single unified framework the epoch of Malthusian stagnation, the modern era of sustained economic growth, and the recent transition between these distinct regimes. Unified growth theory reveals the underlying micro foundations that are consistent with the growth process over the entire history of the human species, enhancing the confidence in the viability of the theory, its predictions and policy implications for the growth process of less developed economies.—Growth ; Technological Progress ; Demographic Transition ; Income Distribution ; Human Capital ; Evolution ; Natural Selection ; Malthusian Stagnation ; Class Structure
Keywords: O11; O14; O33; O40; J11; J13; 330; Wachstumstheorie